Prawosławne cerkwie Grodna w czasach Rzeczypospolitej Obojga Narodów - Sawicki, Piotr (Przegląd Środkowo-Wschodni, 2023)
The article shows the fate of the Grodno Orthodox churches after the introduction of the Union of Brest into the territory of the Polish-Lithuanian Commonwealth. It describes the process of annexation of Orthodox churches by the Uniate Church and the Roman Catholic Church and raises the issue of assuming possession of the church lands. The aim of the article is not only to present the degradation of the material heritage of the Orthodox Church, but also to illustrate the reasons for the confessional and ethnic transformation of Grodno reflected in the sacred architecture of this city.